Dietary γ-mangostin triggers immunogenic cell death and activates cGAS signaling in acute myeloid leukemia - Zi-Jie Long; Jun-Dan Wang; Sheng-Xiang Qiu; Yi Zhang; Si-Jin Wu; Xin-Xing Lei; Ze-Wei Huang; Jia-Jie Chen; Yong-Liang Yang; Xiang-Zhong Zhang; Quentin Liu (Elsevier, 2023)
Immunogenic cell death (ICD), one of cell-death types through release of damage-associated molecular patterns from dying tumor cells, activates tumor-specific immune response and elicits anti-tumor immunity by traditional radiotherapy and chemotherapy. However, whether natural products could induce ICD in leukemia is not elucidated. Here, we report dietary γ-mangostin eradicates murine primary leukemic cells and prolongs the survival of leukemic mice. As well, it restrains primary leukemic cells and CD34+ leukemic progenitor cells from leukemia patients. Strikingly, γ-mangostin attenuates leukemic cells by inducing ICD as characterized by expression of HSP90B1, ANXA1 and IL1B. Additionally, γ-mangostin accelerates cytoplasmic chromatin fragments generation, promoting DNA damage response, and enhances cGAS activation, leading to up-regulation of chemokines. Meanwhile, it induces HDAC4 degradation and acetylated histone H3 accumulation, which promotes chemokines transcription. Ultimately, CD8+ T cell is activated and recruited by γ-mangostin-induced chemokines in the microenvironment. Our study identifies γ-mangostin triggers ICD and activates cGAS signaling through DNA damage response and epigenetic modification. Therefore, dietary γ-mangostin would act as a potential agent to provoke anti-tumor immunity in the prevention and treatment of leukemia.